Assessment of the technical-economic performance and optimization of a parabolic trough solar power plant under Algerian climatic conditions - Khaled Bouchareb; Nabila Ihaddadene; Khellaf Belkhiri; Khaoula Ikhlef; Aissa Boudilmi (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
In this study, the design, analysis and optimization of the performance of a concentrated solar power plant that is based on the parabolic trough technology with a capacity of 100 MW equipped with a thermal energy storage system were conducted, in two representative sites in Algeria (Tamanrasset and M’Sila). The System Advisor Model software is used to evaluate the technical and economic performances of the two proposed power plants, in addition to carrying out the process of optimizing the initial design of the two power plants by finding the optimal values of the solar multiple and full load hours of the thermal energy storage system, with the aim of increasing the annual energy production and reducing the levelized cost of electricity. The results of the performance analysis conducted on the optimized design showed that the optimum values of the solar multiple and full load hours of the thermal energy storage system for the proposed power plant at the Tamanrasset site were found to be 2.4 and 7 h, respectively, with an annual electricity production of 514.6 GWh, and a minimum value of the levelized cost of electricity of 6.3¢/kWh. While the optimum performance of the proposed plant at the M'Sila site can be achieved by selecting a solar multiple of 3 and 7 h for thermal energy storage system, with a high annual energy production of 451.84 GWh and a low value of the levelized cost of electricity of 7.8¢/kWh. The results demonstrate that CSP plants using parabolic trough technology can increase energy security in the country, while reducing environmental concerns associated with the use of fossil materials.